Long Non-Coding RNA LINC00152 Regulates Self-Renewal of Leukemia Stem Cells and Induces Chemo-Resistance in Acute Myeloid Leukemia - Cui, Chunhong; Wang, Yan; Gong, Wenjie; He, Haiju; Zhang, Hao; Shi, Wei; Wang, Hui (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) relapse has a very poor prognosis and remain a common cause of treatment failure in this disease. Relapsed AML is partially driven by chemo-resistant nature of leukemia stem cells (LSCs). The underlying molecular mechanisms are still not fully understood. Evidence accumulated over the past decades shows that long non-coding RNAs (lncRNAs) has a crucial role in AML development. Here we identified an lncRNA, LINC00152, which was highly expressed in CD34+ LSCs and regulated self-renewal of leukemia stem cells derived from AML patients. Importantly, LINC00152 upregulation was correlated with expression of 16 genes out of a 17-gene LSC (LSC17) biomarker, which contributed to accurate prediction of initial therapy resistance in AML. The knockdown of LINC00152 markedly increased drug sensitivity of leukemia cells. Furthermore, we found expression of LINC00152 was correlated with poly-ADP-ribose polymerase 1 (PARP1) expression in AML and knockdown of LINC00152 significantly decrease expression of PARP1; upregulation of LINC00152 or PARP1 was all associated with poor prognosis in AML patients. Collectively, our data highlight the importance and mechanism of LINC00152 in the regulation of self-renewal and chemo-resistant characteristic of LSCs in AML.